Желательно по действиям и понятно

ленок352 ленок352    2   07.12.2019 16:38    0

Ответы
капллпвраае1 капллпвраае1  10.10.2020 19:09

1) (x-4)(x+2)-(x-5)(x+6)= -x

x²+2x-4x-8-x²-6x+5x+30+x=0

-2x+22=0

x=11

2) 12x²-(3x-4)(4x+1)=19

12x²-12x²-3x+16x+4-19=0

13x-15=0

x=15/13

ПОКАЗАТЬ ОТВЕТЫ
bodleva06 bodleva06  10.10.2020 19:09

(x-4)(x+2)-(x-5)(x+6)=-x

x^{2}-2x-8-(x^{2}+x-30)=-x

x^{2}-2x-8-x^{2} -x+30+x=0

-2x+22=0

-2x=-22

x=11

ответ: 11

__________________________________________________________

12x^{2} -(3x-4)(4x+1)=19

12x^{2}-(12x^{2}-13x-4)=19

12x^{2}-12x^{2}+13x+4-19=0

13x-15=0

13x=15

x=15/13

ответ: 15/13

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика